Szczególny przypadek recepcji gnozy w Polsce. Jerzego Prokopiuka poszukiwanie duchowości - Jocz, Artur (Polskie Towarzystwo Religioznawcze, 2016)
When describing the presence of gnosis in Polish culture it is impossible not to mention Jerzy Prokopiuk (born 1931). However, his work shouldn’t be reduced just to its huge translatory, publishing and popularization legacy. It is also worth to note his personal spiritual, intellectual and gnostic searches and to relate them to the history of the reception of gnosis in Poland. Thus, the aim of these remarks is an attempt to reconstruct Prokopiuk’s reflections on the essence of God, the nature of the world and the human phenomenon.
Keywords: gnoza; antropozofia; demiurg; cierpienie; transracjonalność